1994
DOI: 10.1111/j.1365-3180.1994.tb01997.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nitrogen on growth and photosynthesis of sorghum infected with Striga hermonthica from different provenances

Abstract: The influence of Striga hermonthica on sorghum growth and photosynthesis is dependent on the provenance of the parasite seed. Inter-provenance differences are correlated with emergence time of the parasite above ground, as well as with the mass (but not number) of Striga hermonthica plants supported by the host. The greater effects of early attachment on host growth and photosynthesis were demonstrated by inoculating S. hermonthica plants to both 3-day-old and 19-day-old hosts. There were statistically signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 14 publications
3
30
2
Order By: Relevance
“…Early infection (18 dap) of ' CSH-1 ' had a more severe effect on photosynthesis and biomass accumulation than delayed infection (28 and 38 dap). Few studies have examined the effects of delayed infection of cereals but these results support preliminary laboratory observations by Cechin & Press (1993a) where biomass accumulation in sorghum plants infected with S. hermonthica when 3 d old was lower than in those infected when 19 d old. Field studies manipulating the time of Striga attachment have also been undertaken using acetolactate synthase inhibiting herbicides.…”
Section: supporting
confidence: 63%
See 2 more Smart Citations
“…Early infection (18 dap) of ' CSH-1 ' had a more severe effect on photosynthesis and biomass accumulation than delayed infection (28 and 38 dap). Few studies have examined the effects of delayed infection of cereals but these results support preliminary laboratory observations by Cechin & Press (1993a) where biomass accumulation in sorghum plants infected with S. hermonthica when 3 d old was lower than in those infected when 19 d old. Field studies manipulating the time of Striga attachment have also been undertaken using acetolactate synthase inhibiting herbicides.…”
Section: supporting
confidence: 63%
“…Grain yields were significantly greater where parasite emergence was delayed (Abayo et al, 1996). Cechin & Press (1993a) suggested that the age at which a plant becomes infected by S. hermonthica might be an important determinant of the extent to which the parasite can affect host productivity. Laboratory results for Striga-susceptible ' CSH-1 ' and ' SRN-39 ' but not apparently for ' Ochuti ', support this hypothesis.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…The cultivar TZEE-W Pop STR C 5 was identified as high yielding and stable both under multiple-stress and nonstress environments suggesting that it has a broad adaptation to the growing environments in WCA. The results of this study are of special interest because drought, low-N, and Striga occur simultaneously under field conditions in WCA and when this happens, the combined effect can be devastating (Cechin and Press, 1993;Kim and Adetimirin, 1997;Badu-Apraku et al, 2015b). The superior performance of the cultivars under varying environmental conditions is of utmost importance as maize varieties targeted to the drought-prone areas of WCA must also be tolerant to low-N, resistant/tolerant to Striga and have competitive yield under non-stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Benth is a major constraint to maize production in the savannas of WA. In the farmer's fi eld, drought, Striga infestation, and soil nutrient defi ciency can occur simultaneously, with a devastating combined eff ect (Cechin and Press, 1993;Kim and Adetimirin, 1997;Badu-Apraku et al, 2011b). Th erefore, maize varieties targeted to the Striga-prone areas of WCA must also be resistant or at least tolerant to drought and low-N.…”
mentioning
confidence: 99%